Oketani Massage on the Continuity of Breastfeeding Mothers - Andri, Juli; Maryanto, Qori; Padila, Padila; Sugiharno, Ramadhan Trybahari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of oketani massage on smooth breastfeeding in breastfeeding mothers at the Basuki Rahmat Community Health Center, Bengkulu City. This research is quantitative research with a